Microbial Degradation of Cephalothin by Cephalothin-Susceptible Escherichia coli - Nishiura, Tsuneo (1978)
Cephalothin (CET)-susceptible Escherichia coli, which can degrade CET after prolonged incubation in broth containing a concentration of the drug greater than the minimum inhibitory concentration, was found in a clinical specimen. The substrate specificity of the partially purified enzyme to cephalosporin analogs strongly indicated the occurrence of CET-specific degradation. Nuclear magnetic resonance analysis of the degradation reaction demonstrated the appearance of two new signals attributed to deacetyl CET. This suggests the possibility of the presence of acylesterase.